Receptor signaling integration by TRP channelsomes - Mori, Yasuo; Kajimoto, Taketoshi; Nakao, Akito; Takahashi, Nobuaki; Kiyonaka, Shigeki (Advances in experimental medicine and biology, 2011)
Homologues of transient receptor potential (TRP) genes encode a variety of cation channels, most of which conduct Ca(2+) across the plasma membrane. TRP proteins interact with a variety of proteins and other biologically important factors, such as second messengers, and thereby form "channelsomes", most of which function as Ca(2+) signalsomes. Activation mechanisms and final outputs are exquisitely incorporated in the signaling system of TRP channelsomes. In this study, we discuss the channelsomes of TRPC3, TRPC5, and TRPM2, which show unique molecular interactions and modulations of activation. Comparative studies of these specific TRP channelsomes should aid the determination of general rules that govern the formation and regulation of channelsomes and signalsomes.